666. Microbial Cell-Free DNA Sequencing for Evaluation of Response to Antibiotic Therapy in Patients with Relapsed or Refractory Leukemia. (31st December 2020) - Wolf, Joshua; Goggin, Kathryn; griffen, Amanda; Kohler, Christina; Allison, Kim J; Inaba, Yuki; Ahmed, Asim A; Hollemon, Desiree D; Brenner, Abigail; Maron, Gabriela; Maron, Gabriela; Sun, Yilun; et al.
Abstract: Background: In patients with bloodstream infection (BSI), true eradication of infection takes longer than blood culture clearance. Therefore, optimal treatment duration, especially in immunocompromised hosts, is unknown. A sensitive test of microbiological response to treatment could improve care by indicating a time for safe antibiotic discontinuation. Microbial cell-free DNA sequencing (mcfDNA-seq) is a sensitive predictor of BSI, and we hypothesize that it might also be useful to measure response to treatment. Methods: Eligible participants were < 25 years of age being treated for leukemia. Remnant plasma samples were collected as part of a prospective study (PREDSEQ), and underwent mcfDNA-seq by Karius Inc. in a CLIA/CAP-accredited laboratory. Pathogen DNA was reported in molecules per microliter (MPM). Testing was batched and blinded. Available samples from Day 1 through Day 7 after onset of bacterial BSI were included. We evaluated decay of the BSI pathogen DNA after initiation of effective antibiotic therapy, from the peak to last available sample, and compared episodes with slow (< 0.5 log10 MPM/day) vs. rapid DNA decay. Results: There were 13 evaluable BSI episodes in 9 participants; 7 had slow DNA decay. Persistence of bacteremia or fever ≥1 day after initiation of effective antibiotics occurred in 9/13 episodes (7/7 slow decay and 2/6 rapid decay; P = 0.02). Slow decay persisted beyond resolution of bacteremia and fever in 3/7 of these cases. Figure 1. Pathogen DNA Concentration by mcfDNA-seq During Antibiotic Treatment of Bacteremia; Dashed line, blood culture positive; Red circle, last fever Conclusion: In this small convenience sample of patients with leukemia, slow mcfDNA-seq DNA decay correlated with persistent fever or bacteremia. Post-BSI mcfDNA-seq monitoring should be investigated with the goal of decreasing inappropriate antibiotic therapy and preventing treatment failure. Disclosures: Joshua Wolf, MBBS, PhD, FRACP, Karius inc (Grant/Research Support) Asim A. Ahmed, MD, Karius (Employee) Desiree D. Hollemon, MSN, MPH, Karius inc (Employee) Charles Gawad, MD PhD, Karius inc (Grant/Research Support)